2014
DOI: 10.1097/wnr.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

D609-mediated inhibition of ATP synthesis in neural progenitor cells

Abstract: D609 (Tricyclodecan-9-yl-xanthogenate) is an anti-oxidative molecule exhibiting antiproliferative and neuroprotective properties in a variety of cells. Previously we have shown that D609 decreased the proliferation of neural progenitor cells. In this study we examined the anti-oxidative property of D609 on neural progenitor cells isolated from the subventricular zone of the rat brain. Cellular oxidation was assessed by measuring the ATP content of the cells. Our results show that D609 decreased the ATP content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Even though studies have shown that NSCs function at a lower metabolic rate when compared to other cells, a decreased level of intracellular NSC ATP can inhibit the overall process of NSC proliferation 39 . Recent studies have shown how various molecules that inhibit the actions of ATP, such as tricyclodecan-9-yl-xanthogenate (D609), decrease the rate of proliferation among NSCs, therefore opposing the process of proliferation 40 . Moreover in vitro results indicated that EFV lowered NSC MMP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Even though studies have shown that NSCs function at a lower metabolic rate when compared to other cells, a decreased level of intracellular NSC ATP can inhibit the overall process of NSC proliferation 39 . Recent studies have shown how various molecules that inhibit the actions of ATP, such as tricyclodecan-9-yl-xanthogenate (D609), decrease the rate of proliferation among NSCs, therefore opposing the process of proliferation 40 . Moreover in vitro results indicated that EFV lowered NSC MMP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Modulating COX activity can thus interfere with ATP production, influencing cell proliferation. After the incubation of D609 neural progenitor cells, cytochrome C oxidase activity was found to decrease, supporting this hypothesis [ 128 , 129 ]. According to these findings, D609 can inhibit cytochrome C oxidase activity and, as a result, ATP synthesis in neural progenitor cells [ 129 ].…”
Section: Pharmacological Properties Of D609mentioning
confidence: 66%
“…Tricyclodecan-9-yl-xanthogenate (D609), an inhibitor for phosphatidylcholine-specific phospholipase C, exhibits diverse potent biological functions 8 , 9 . It has been shown that D609 can act as a GSH mimetic compound to scavenge hydrogen peroxide and hydroxyl free radicals 10 .…”
Section: Introductionmentioning
confidence: 99%